2003
DOI: 10.4141/p02-172
|View full text |Cite
|
Sign up to set email alerts
|

Chemical maturation and storage performance of eleven Russet Burbank clones

Abstract: S. 2003. Chemical maturation and storage performance of eleven Russet Burbank clones. Can. J. Plant Sci. 83: 893-902. Although introduced as a cultivar from a somaclonal mutation of smooth Burbank in the 19th century, the subsequent identification and commercial selection of distinct Russet Burbank clones or strains has not been evident in the scientific literature. The present study examined chemical maturity of tubers (sucrose rating values and glucose content) and subsequent storage performance over a 3-yr … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…While giant hill mutants of 'Russet Burbank' have not been selected, there is evidence that different germplasm accessions of 'Russet Burbank' held at various repositories in North America are essentially geographic variants, grown for decades at different locations. Accessions differed in yield and processing components (Wright and Mellor 1976;Love et al 1992;Coleman et al 2003). The New Brunswick accession of 'Russet Burbank' (NB 'Russet Burbank') is paramount in Atlantic Canada.…”
mentioning
confidence: 99%
“…While giant hill mutants of 'Russet Burbank' have not been selected, there is evidence that different germplasm accessions of 'Russet Burbank' held at various repositories in North America are essentially geographic variants, grown for decades at different locations. Accessions differed in yield and processing components (Wright and Mellor 1976;Love et al 1992;Coleman et al 2003). The New Brunswick accession of 'Russet Burbank' (NB 'Russet Burbank') is paramount in Atlantic Canada.…”
mentioning
confidence: 99%
“…Somaclonal variation is known to occur within clonally propagated potato. Within Russet Burbank there exist several distinct clones selected from field populations over many decades of production around the world that are regarded to possess distinctive traits of value to local production regions (Coleman et al, 2003). These include some variation in common scab disease resistance (Wilson, 2001), although none possess extreme resistance to this disease.…”
Section: Discussionmentioning
confidence: 99%
“…Many SSR markers have been identified and successfully used in fingerprinting potato DNA (Veilleux et al 1995;Kawchuk et al 1996;Milbourne et al 1998;Coleman et al 2003;Ghislain et al 2004;Coombs et al 2004). For example, Veilleux et al (1995) identified seven pairs of SSR primers for potato, by searching GenBank potato DNA sequences; two from a starch synthase gene and one from a patatin pseudogene.…”
mentioning
confidence: 99%